2019
DOI: 10.1007/s13679-019-00340-6
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Measuring and Interpreting Human Appetite (Satiety/Satiation) and Its Contribution to Obesity

Abstract: Purpose of Review The goals of this paper are to report current research practices in investigations of human appetite control and to assess their relationships with emerging theoretical principles. Appetite is often distinguished by the separation of homeostatic and hedonic processes. Recent Findings This report assesses the validity of a homeostatic toolkit to measure subjectively perceived hunger and its relationship to the developing processes of satiation (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 94 publications
1
99
0
3
Order By: Relevance
“…Generally, GLP-1 increases satiety rather than decreasing hunger [43]. Although it is neuropsychologically and neurobiologically difficult to separate decreased hunger from increased satiety, due to overlapping neuroanatomical areas and neuropharmacological regulations [45], in the present study, the increase in satiety appeared earlier (at T90) than the decrease in hunger (at T120 and T150). This might denote the involvement of other orexigenic peptides different from the unchanged ghrelin, which might have been inhibited by amino acids or, more plausibly, by GLP-1 [12,46].…”
Section: Discussionmentioning
confidence: 43%
“…Generally, GLP-1 increases satiety rather than decreasing hunger [43]. Although it is neuropsychologically and neurobiologically difficult to separate decreased hunger from increased satiety, due to overlapping neuroanatomical areas and neuropharmacological regulations [45], in the present study, the increase in satiety appeared earlier (at T90) than the decrease in hunger (at T120 and T150). This might denote the involvement of other orexigenic peptides different from the unchanged ghrelin, which might have been inhibited by amino acids or, more plausibly, by GLP-1 [12,46].…”
Section: Discussionmentioning
confidence: 43%
“…Perceived satiety is described as the period between meals (after food consumption) and the process occurring in that time period (Gibbons et al, 2019). Perceived satiety is measured through visual analogue scales (VAS), in which participants are allowed to place a mark on a 100mm horizontal line to reflect the intensity of their satiety sensation at a particular time (Gibbons et al, 2019). Our study showed that both βG and WP increased perceived satiety and suppressed the feeling of hunger compared with control.…”
Section: Discussionmentioning
confidence: 79%
“…Our study showed that both βG and WP did not further increase perceived satiety and suppressed the feeling of hunger compared with control. Perceived satiety is described as the period between meals (after food consumption) and the process occurring in that time period (Gibbons et al, 2019). Perceived satiety is measured through visual analogue scales (VAS), in which participants are allowed to place a mark on a 100mm horizontal line to reflect the intensity of their satiety sensation at a particular time (Gibbons et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not observe changes in weight gain over the treatment period, VPA-treated mice accumulated significantly greater feeding durations and entries without clear evidence of locomotor suppression, active state dysregulation or increased "sleep". Weight gain is a well-known side effect of VPA and may be explained by increased appetite, although appetite, satiety or hunger are challenging to objectively measure in humans 72 . VPA has been linked to hyperinsulinemia (and insulin resistance), and hyperleptinemia (with leptin resistance), both of which would be expected to increase appetite 58,73 .…”
Section: Discussionmentioning
confidence: 99%